Perencanaan Sumber Daya Manusia pada PT ABC - Endah Kurniawati (Universitas Islam Kadiri, 2022)
Business competition and rapid environmental changes require human resource (HR) practitioners to be able to ensure the availability of employees in accordance with existing demands. This is certainly not something easy. Human resource planning is expected to ensure the availability of employees both in quality and quantity. The purpose of the research is to determine the implementation of human resource planning with all the challenges and efforts to maintain its implementation in accordance with existing procedures. The research was conducted at PT. ABC which is a manufacturing company. The type of research used is descriptive qualitative. Data obtained through in-depth interviews and documentation. The results of the study show that the implementation of human resource planning has been carried out well, although there are a number of challenges and obstacles in its implementation.